Transesterification of palm oil using supercritical methanol with co-solvent HCFC-141b - Hong, Seung Tae; Kim, Jin-Woo; Jang, Won-Ho; Lim, Jong Sung; Park, Hyung Sang; Yoo, Ki-Pung; Apfel, Carolin; Arlt, Wolfgang (Research on Chemical Intermediates, 2009)
The transesterification of palm oil in supercritical methanol has been investigated without using any catalyst. HCFC-141b was used as co-solvent to reduce the molar ratio of methanol to palm oil under the milder conditions. The reaction was carried out in a flow-type tubular reactor. The residence time was fixed at 40 min. When the molar ratio of methanol to palm oil was set to 20:1 at 325 °C and 35 MPa, the optimum molar ratio of methanol to co-solvent was found to be 20:1. Addition of HCFC-141b increased FAME production even at the lower molar ratio of methanol to palm oil. In addition, a similar FAME content was obtained under the milder conditions (5 MPa lower pressure) compared with conditions without co-solvent at higher pressure. The role of HCFC-141b in the transesterification reaction under supercritical conditions was investigated. © Springer Science+Business Media B.V. 2009.
Keywords: Biodiesel; Co-solvent; FAME; HCFC-141b; Supercritical methanol; Transesterification